Clinical and imaging features of pituitary apoplexy and role of imaging in differentiation of clinical mimics - Goyal, Pradeep (Quant Imaging Med Surg, 2018)
To discuss the clinical syndrome, review common imaging findings of pituitary apoplexy (PA) and role of imaging in therapy and follow-up. Also, to review other acute clinical scenarios with similar clinical and/or imaging findings as PA. PA is a severe and potentially life-threatening medical emergency, characterized by constellation of symptoms/signs that occur as a result of acute hemorrhage and/or infarction in pituitary gland. Patients present with acute and sudden onset of symptoms/signs, most commonly with severe headache, vision deficits/ophthalmoplegia, altered mental status, and possible pan hypopituitarism. Pre-existing macro adenoma (65–90%), especially non-functioning and prolactinomas, are most susceptible to apoplexy, which undergoes hemorrhage or infarct, but PA can occur with normal pituitary or microadenoma. Because of the probable grave prognosis of PA, imaging characteristics of PA and other acute clinical scenarios with similar clinical and/or imaging findings should be familiar to radiologists. PA is potentially a life-threatening clinical syndrome, however, imaging and clinical findings can lead the radiologist towards appropriate diagnosis, and rule out other clinical mimics. When hemorrhage is secondary to an underlying lesion, regrowth of the pituitary tumor years after a PA episode is possible and patients require long-term clinical and imaging surveillance.